2022
DOI: 10.48550/arxiv.2204.01198
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antenna Impedance Estimation at MIMO Receivers

Abstract: This paper considers antenna impedance estimation based on training sequences at MIMO receivers.The goal is to firstly leverage extensive resources available in most wireless systems for channel estimation to estimate antenna impedance in real-time. We assume the receiver switches its impedance in a predetermined fashion during each training sequence. Based on voltage observation across the load, a classical estimation framework is developed incorporating the Rayleigh fading assumption. We then derive in close… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Consequently, Wu and Hughes derived a closed-form maximum-likelihood (ML) estimator for impedance, treating the channel gains as nuisance parameters, for both MISO and MIMO receivers under i.i.d. Rayleigh fading [5], [7]. They also demonstrated that these ML estimators are efficient with sufficient signal-to-noise-ratio (SNR) and diversity.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Consequently, Wu and Hughes derived a closed-form maximum-likelihood (ML) estimator for impedance, treating the channel gains as nuisance parameters, for both MISO and MIMO receivers under i.i.d. Rayleigh fading [5], [7]. They also demonstrated that these ML estimators are efficient with sufficient signal-to-noise-ratio (SNR) and diversity.…”
Section: Introductionmentioning
confidence: 95%
“…Due to time-varying near-field loading conditions, antenna impedance may change significantly. Researchers have proposed techniques to estimate the unknown antenna impedance in realtime [2]- [7]. However, it remains unclear when these estimation algorithms should be triggered.…”
Section: Introductionmentioning
confidence: 99%